AI INTEGRATION INTO MEDICAL DISCIPLINES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
A paradigmatic shift in the structure of digital literacy in higher education determines the transition from the utilitarian development of software to the systemic inclusion of artificial intelligence (AI) technologies. This trend is critically important for high-tech medical disciplines (radiology, nuclear medicine), where AI is the modernization of syllabuses (including the experience of integrating ChatGPT Edu at the Icahn School of Medicine at Mount Sinai in 2025) significantly increases the clinical adaptability of graduates. However, the global expansion of innovation is limited by the conservatism of didactic models, the heterogeneity of digital maturity of personnel and infrastructure shortages, which in the context of developing economies (LMIC) exacerbates inequality.